2019
DOI: 10.1007/s11420-018-9636-2
|View full text |Cite|
|
Sign up to set email alerts
|

Opioid-Free Total Knee Arthroplasty? Local Infiltration Analgesia Plus Multimodal Blood-Loss Prevention Make it Possible

Abstract: Opioids have been widely used in the USA for pain control after total knee arthroplasty (TKA). However, adverse effects, especially the possibility of addiction, have increased interest in opioid-free pain management after surgery. We therefore sought to review current pain management protocols after TKA, focusing especially on opioid-free alternatives. We reviewed the literature on pain management after TKA using Medline (PubMed), through June 30, 2018, using the keywords BTKA^and Banalgesia.^We found 388 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Rodriguez-Merchan et al have recently published that local infiltration analgesia (LIA) is a good option for reducing the use of postoperative opioids. Multimodal blood-loss prevention was recommended in combination with opioid-free analgesia [20] .…”
Section: Authors Year Findings Commentsmentioning
confidence: 99%
“…Rodriguez-Merchan et al have recently published that local infiltration analgesia (LIA) is a good option for reducing the use of postoperative opioids. Multimodal blood-loss prevention was recommended in combination with opioid-free analgesia [20] .…”
Section: Authors Year Findings Commentsmentioning
confidence: 99%
“…Multimodal pain regimens have gained popularity in recent years in an effort to improve postoperative pain control while simultaneously reducing reliance on opioid medications [14][15][16][17][18]. These regimens utilize local anesthetics, peripheral nerve blocks, and non-narcotic alternatives for effective pain control.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Several techniques had been used for postoperative pain relief, such as intravenous opioids, peripheral nerve block, epidural analgesia, adductor block, femoral nerve block (FNB), and periarticular infiltration analgesia (PIA). [7][8][9][10] While it has been reported that implementing FNB with a risk of injuring the nerve, influencing quadriceps function, as well as benefiting the area of the femoral nerve only. [11] The PIA has been used over the last decade for postoperative analgesia following TKA.…”
Section: Introductionmentioning
confidence: 99%